THE INFLUENCE OF VARIOUS RISK FACTORS RELATED TO METABOLIC DISORDERS ON COGNITIVE FUNCTION IN THE ELDERLY GROUP - Tadjudin, Noer Saelan; Gunaidi, Farell Christian; Kurniawan, Junius; Sunjaya, Anthony Paulo; Sunjaya, Angela Felicia (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2024)
Dementia is a condition characterized by significant impairment in at least one domain of cognition, including executive function, complex attention, language, learning, memory, perceptual-motor, or social cognition. Risk factors for vascular dementia include smoking, hyperlipidemia, hypertension, diabetes, atrial fibrillation, obesity, and lack of exercise. This study aims to examine the relationship between metabolic disorders and dementia in the elderly. The design of this research was cross-sectional at the Hana Nursing Home in January 2024, with inclusion criteria in the form of an elderly group of at least 60 years. The independent variables in this study were blood pressure, hemoglobin, hematocrit, body mass index, cholesterol, uric acid, and random blood sugar. The dependent variable in this study includes the Mini-Mental State Examination (MMSE) score. This study included 61 respondents who met the inclusion criteria. The results of the multiple linear regression statistical test (Backward LR) with 6 stages stated that body mass index (p-value: 0.001; B: 0.281) and hematocrit (p-value: 0.011; B: 0.528) played a significant role in decreasing the value MMSE. The conclusion of this study is that body mass index, and hematocrit are related to dementia. This research opens up insight into the importance of controlling body weight and body composition, especially in the elderly group to prevent decline in cognitive function in old age.